Re-examining provider perceptions of best pre-war practices: what elements can help opiate agonist therapy programs in Ukraine successfully survive the crisis? - Dellamura, P.; Meteliuk, A.; Fomenko, T.; Rozanova, J. (Frontiers in Public Health, 2024)
Purpose This paper seeks to explore and understand what constitutes successful opioid agonist therapy (OAT) programs from the views of Ukrainian OAT providers in their context-specific accounts. Prior to the ongoing war the Ukrainian addiction treatment system made great strides to expand its OAT program and increase the number of patients. Since the beginning of the war there has been much alarm that those hard-earned successes will be destroyed. However, emerging evidence suggests that the Ukrainian OAT programs have shown signs of resilience in the face of adversity albeit at great cost. What aspects of the OAT programs developed prior to the crisis have been helpful to allow them to weather the storm? Using the data from 24 addiction treatment providers, this paper describes the essential elements of the OAT programs that preceded the current crisis which made them robust over time. By examining the narratives of the participants interviewed pre-war and pre-COVID-19 the paper reveals structural and cultural elements of the OAT programs before the perfect storm that are likely to endure. To the best of our knowledge, no one else has investigated OAT providers perspectives in Ukraine prior to the crisis which makes this paper extremely salient to understand both the robustness and the vulnerability of MAT programs in Ukraine during the war and going forward. Methodology The data come from qualitative semi-structured interviews with 24 OAT providers throughout 5 regions of Ukraine. Participants included front-line clinicians, head narcologists, and chief doctors from TB clinics, district hospitals and drug addiction centers. Using a coding scheme of 103 inductively developed categories we explored participants’ perceptions of their OAT program. Findings In the stories shared by clinicians pre crisis, three major interconnected themes focused on economic uncertainty at the institutional level (leading to under-staffing), structural capacity of the program, and clinicians’ professional identity, shaping differing views on application of rules for administrative discharge, take-home dosing, and the potential for scale-up. Knowing the data collection was completely unbiased to the current crisis, interpreting the findings helps us understand that OAT clinicians have had “years” of training under conditions of duress in Ukraine to overcome barriers, find creative solutions and form a support network that became indispensable in surviving the current humanitarian catastrophe. Conclusion In the discussion we point out that the current crisis magnified the pre-existing challenges as the providers approach toward overcoming them was already largely present before the crisis (just on a different scale). The underlying fragility of resources was a constant since OAT inception in Ukraine. Historically, providers in Ukraine operated in a system that was under-funded in the absence of solid governmental funding for OAT programs, yet they came up with solutions which required ingenuity that they took pride in. This gives hope that addiction treatment in Ukraine and OAT programs will not be casualties of this humanitarian crisis and providers and their patients will persevere.